In vivo intrinsic optical signal imaging of mouse retinas - Wang, Benquan (Proc SPIE Int Soc Opt Eng, 2016)
Intrinsic optical signal (IOS) imaging is a promising noninvasive method for advanced study and diagnosis of eye diseases. Before pursuing clinical applications, more IOS studies employing animal models are necessary to establish the relationship between IOS distortions and eye diseases. Ample mouse models are available for investigating the relationship between IOS distortions and eye diseases. However, in vivo IOS imaging of mouse retinas is challenging due to the small ocular lens (compared to frog eyes) and inevitable eye movements. We report here in vivo IOS imaging of mouse retinas using a custom-designed functional OCT. The OCT system provided high resolution (3 μm) and high speed (up to 500 frames/s) imaging of mouse retinas. An animal holder equipped with a custom designed ear bar and bite bar was used to minimize eye movement due to breathing and heartbeats. Residual eye movement in OCT images was further compensated by accurate image registration. Dynamic OCT imaging revealed rapid IOSs from photoreceptor outer segments immediately (<10 ms) after the stimulation delivery, and unambiguous IOS changes were also observed from inner retinal layers with delayed time courses compared to that of photoreceptor IOSs.